Trends in child and adolescent obesity prevalence in economically advanced countries according to socioeconomic position: a systematic review. (23rd December 2015) - Chung, A.; Backholer, K.; Wong, E.; Palermo, C.; Keating, C.; Peeters, A.
Summary: Recent obesity trends in children and adolescents suggest a plateau. However, it is unclear whether such trends have been experienced across socioeconomic groups. We analysed whether recent trends in child and adolescent overweight and obesity differ by socioeconomic position (SEP) across economically advanced countries. Eligible studies reported overweight and obesity prevalence in children and/or adolescents (2–18 years), for at least two time points since 1990, stratified by SEP. Socioeconomic differences in trends in child and adolescent overweight and obesity over time were analysed. Differences in trends between SEP groups were observed across a majority of studies. Over half the studies indicated increasing prevalence among low SEP children and adolescents compared to a third of studies among children and adolescents with a high SEP. Around half the studies indicated widening socioeconomic inequalities in overweight and obesity. Since 2000 a majority of studies demonstrated no change or a decrease in prevalence among both high and low SEP groups. However around 40% of studies indicated widening of socioeconomic inequalities post‐2000. While our study provides grounds for optimism, socioeconomic inequalities in overweight and obesity continue to widen. These findings highlight the need for greater consideration of different population groups when implementing obesity interventions. © 2015 World Obesity